Configurations and Efficiency of Plumbing Systems in High-Rise Buildings: A Systematic Literature Review and Scopus based publication trends (2000–2025) - Zufri Hasrudy Siregar; Arif Fadillah Nasution; Yuri Dwi Lianto; Refiza (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2026)
High-rise building plumbing systems face increasing challenges related to hydraulic efficiency, energy consumption, and sustainable water management. This study aims to analyze the evolution of plumbing system configurations, efficiency strategies, and emerging research trends through a Systematic Literature Review and bibliometric analysis of Scopus-indexed publications from 2000–2025. The novelty of this research lies in integrating hydraulic engineering, smart building technology, IoT, and AI within a unified analytical framework focused on tropical high-rise buildings. PRISMA methodology, Bibliometrix-R, and VOSviewer were employed to evaluate 751 documents. The results reveal rapid growth in smart plumbing research, emphasizing energy optimization, digital monitoring, and AI-based water management systems.